The Impact of Islamic Financial Literacy, Perception of Convenience, and Hedonism on the Behavior of Muslim Students: A Multigroup Analysis - Shofa, Devy Midayatus; Berakon, Izra (Islamic Social Finance, 2025)
This study aims to examine the influence of Islamic financial literacy, perception of convenience, and hedonism on Islamic financial behavior in the use of digital wallets whether there is a difference in interest in using services between men and women. The source of data for this study is primary data obtained from distributing questionnaires, in this study as many as 190 respondents with the purposive sampling method. The object of this research is a Muslim student who lives in Yogyakarta. The analysis used in this study is PLS-SEM using WARP-PLS software with the gender Multi Group Analysis (MGA) method. The results of the study show that Islamic financial literacy has a significant positive effect on the behavior of using digital wallets. Meanwhile, the perception of convenience and hedonism have a significant positive effect on the behavior of using digital wallets. And there is no difference between men and women in the behavior of using digital wallets seen from the factors of Islamic financial literacy, perception of convenience, and hedonism.